Multi-Parameter Integrated Optical Sensor Based on Multimode Interference and Microring Resonator Structures - Le, Trung Thanh (International Frequency Sensor Association (IFSA) Publishing, 2020)
The ‘Advances in Optics: Reviews’ Book Series is published as an Open Access Books in order to significantly increase the reach and impact of these volumes, which also published in two formats: electronic (pdf) with full-color illustrations and print (paperback). The third of three volumes of this Book Series has organized by topics of high interest. In order to offer a fast and easy reading of each topic, every chapter in this book is independent and self-contained. All chapters have the same structure: first an introduction to specific topic under study; second particular field description including sensing or/and measuring applications. Each of chapter is ending by complete list of carefully selected references with books, journals, conference proceedings and web sites. The Vol.3 is devoted to various topics of applied optics and contains 17 chapters written by 49 experts in the field from 14 countries: Australia, China, India, Israel, Italy, Japan, Malaysia, Mexico, The Netherlands, Poland, Taiwan, UK, USA and Vietnam. ‘Advances in Optics: Reviews’ Book Series is a comprehensive study of the field of optics, which provides readers with the most up-to-date coverage of optics, photonics and lasers with a good balance of practical and theoretical aspects. Directed towards both physicists and engineers this Book Series is also suitable for audiences focusing on applications of optics. A clear comprehensive presentation makes these books work well as both a teaching resources and a reference books. The book is intended for researchers and scientists in physics and optics, in academia and industry, as well as postgraduate students.